Potential Health Benefits of a Pomegranate Extract, Rich in Phenolic Compounds, in Intestinal Inflammation - Raffaele, Marco; Greish, Khaled; Vanella, Luca; Carota, Giuseppe; Bahman, Fatemah; Bindayna, Khalid M.; Ezzat, Hicham; Salerno, Loredana; Pittalà, Valeria; Ballistreri, Gabriele; Amenta, Margherita; Sorrenti, Valeria (Current Nutrition & Food Science, 2021)
Background: Pomegranate is a fruit rich in bioactive compounds such as punicalagins, gallic acid, and ellagic acid derivatives. It has been widely used since ancient times in traditional medicine for a wide variety of diseases. It has been reported that bioactive compounds, such as polyphenols, are able to induce the expression of cytoprotective enzymes, including HO-1. The contribution of HO-1 activity to the prevention of intestinal inflammation has been shown in different models of Inflammatory bowel diseases (IBD). Objective: Aim of the present research was to investigate the molecular mechanisms involved in the beneficial effects of a pomegranate extract (PE), rich in bioactive compounds in intestinal inflammation. Methods: Caco-2 cells exposed to LPS and DSS induced colitis were chosen as convenient experimental models of intestinal inflammation. Results: Results obtained in our experimental conditions showed that PE in vitro was able to induce HO-1 and to reduce cellular damage and oxidative stress through an increase of GSH levels. Moreover, PE was able to decrease the pro-inflammatory marker IL-8 levels and activate TIGAR pathway. The results obtained in vivo, in agreement with the data obtained in vitro, highlighted the ability of PE to reduce intestinal inflammation, preserve the colon length and histological features and reduce IL-6 levels compared to the DSS treated group. Conclusion: PE, rich in bioactive compounds, could contribute, as a supportive therapy, to enhance the effects of the conventional therapeutic strategies on the management of IBD.
Keywords: Pomegranate